The Revivalist Movement and the Emergence of Nationalism in the Islamic World - Zahiroh, Zakiyatuz (Maliki Interdisciplinary Journal, 2025)
Revivalism is a movement of renewal or revival in Islam, and tends to be understood as an effort to revive the spirit of religion as before. Esposito wrote in his book that 'this revivalist movement is a search for identity, authenticity, and tradition'. This revivalism is closely related to fundamentalism. Because this movement emerged as a response to the impact caused by modernism and secularism in religious and political life. And Islamic revivalism is the impact of the failure of classical Islamic modernism, which turned out to be unable to bring society and the Islamic world in accordance with the teachings of Islam itself. The factors causing the emergence of this revivalist movement are not far from internal and external factors. Some examples of revivalist movements in Indonesia include Nahdhotul Ulama' (NU), Muhammadiyah, and Jam'iyah Khair. And the relationship between revivalism and nationalism is very close and complex, often both support and move each other.